Fifty Shades of Grey - James, E L (London Arrow Books, 2012)
When literature student Anastasia Steele is drafted to interview the successful young entrepreneur Christian Grey for her campus magazine, she finds him attractive, enigmatic and intimidating. Convinced their meeting went badly, she tries to put Grey out of her mind--until he happens to turn up at the out-of-town hardware store where she works part-time.
Keywords: Man-woman Relationships -- College Students